In-Situ and In-Operando Experiments. Issue 2 (4th March 2017) - Guo, Jinghua; Crumlin, Ethan
Abstract : How do we learn about the electronic and atomic characteristics of novel materials for efficient solar energy conversion (photovoltaics and water-splitting), energy storage (Li-ion batteries and multivalent-ion batteries), and efficient catalytic activity and selectivity in catalysis? The fundamental scientific problems that we plan to understand and ultimately control are: (1) efficient absorption-induced electron-hole pair formation and its separation at the complex interfaces; (2) bandgap, band levels, and band structure of earth abundant materials that are of crucial importance in electrochemical and photocatalytic applications.